إدارة تعليم اللغة العربية في الدورة المكثفة بمركز الكافة باميكاسان - Ach. Fadoli; Authar, Nailul; Kholid, Nur (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Good educational management will influence the quality of education for students in order to produce graduates who are competitive. The aim of this research is to describe the management of the course program at the Elkaffah Center, including planning, organizing, driving and supervising. This research uses a qualitative approach with a case study type of research. Data collection was carried out through interviews, observation and documentation. As for the results of this research, program planning implemented in intensive courses includes curriculum design, creating a study plan outline, making learning plans for teachers, arranging learning schedules and setting goals to be achieved. The implementation of intensive courses takes place every day so that the evaluations carried out include program evaluations and learning evaluations. Learning evaluation is carried out every day except Saturday and Sunday by dividing it into two parts, namely a written test and an oral test. The evaluation related to the management of the intensive course program itself is carried out after the course process ends in one period.